American Economic Association Universal Academic Questionnaire Summary Statistics - Scott, Charles E; Siegfried, John J (American Economic Review, 2006)
American Economic Association Universal Academic Questionnaire Summary Statistics by Charles E. Scott and John J. Siegfried. Published in volume 96, issue 2, pages 527-530 of American Economic Review, May 2006